Cpw Photo Warehouse: a custom database to facilitate archiving, identifying, summarizing and managing photo data collected from camera traps. Issue 4 (18th December 2015) - Ivan, Jacob S.; Newkirk, Eric S.
Summary: Contemporary methods for sampling wildlife populations include the use of remotely triggered wildlife cameras (i.e., camera traps). Such methods often result in the collection of hundreds of thousands of photos that must be identified, archived, and transformed into data formats required for statistical analyses. Cpw Photo Warehouse is a freely available software based in Microsoft Access ® that has been customized for this purpose using Visual Basic ® for Applications (VBA) code. Users navigate a series of point‐and‐click menu items that allow them to input information from camera deployments, automatically import photos (and image data stored within the photos) related to those deployments, and store data within a relational database. Images are seamlessly incorporated into the database windows, but are stored separately from the database. The database includes menu options that (i) facilitate identification of species within the images, (ii) allow users to view and filter any subset of the databased on study area, species, season, etc., and (iii) produce input files for common analyses such as occupancy, abundance, density and activity patterns using Programs mark, presence, density and the r packages 'secr' and 'overlap'. Our database makes explicit use of multiple observers, which greatly enhances the efficiency and accuracy with which a large number of photos can be identified. Modular subsets of the data can be distributed to an unlimited number of observers on or off site for identification. Modules are then re‐incorporated into the database using a custom import function.